ECOLOGICAL DRYING OF FINE MATERIALS (Conferencea, 2022)
The paper studies the possibility of environmentally friendly drying of fine materials in a contact dryer with a fast-rotating rotor. An equation for calculating a rotary dryer is given. The possibility of organizing wear-free drying during continuous operation of the device is shown.